Effect of Sonication to Protein Extraction from Jackfruit Seed (Artocarpus Heterophyllus) Flour - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Ultrasound technology is growing rapidly in the field of research and development of non-thermal food processing methods. Jackfruit seeds are not only nutritive, but also tasty. The flour from seeds is a fruit residue featuring alternative protein, carbohydrate and fiber source. A wide range of ultrasound power, treatment temperature, treatment time, ratio of liquid: solid have been investigated. Optimum conditions for the extraction of protein were found to be: sonication power of 30 W/g, sonication time 3 min, sonication temperature 45oC and solid-liquid ratio of 2.0: 1.0, and the extraction time of 30 min. Ultrasound is one of the emerging technologies that were developed to reduce the cost and time of processing. It ensures the quality and safety of food products. The use of ultrasound can enhance the extraction process by increasing the mass transfer between the solvent and plant material. Ultrasound in the use of plant extraction has benefits in increased mass transfer, better solvent penetration, less dependence on solvent used, extraction at lower temperatures, faster extraction rates and greater yields of product.Keywords: Jackfruit, Protein, Extraction, Sonication.